The effect of disinfectants on dimensional stability of addition and condensation silicone impressions - Sinobad Tamara; Obradović-Đuričić Kosovka; Nikolić Zoran; Dodić Slobodan; Lazić Vojkan; Sinobad Vladimir; Jesenko-Rokvić Aleksandra (Vojnosanitetski Pregled)
Background/Aim. Dimensional stability and accuracy of an impression after chemical disinfection by immersion in disinfectants are crucial for the accuracy of final prosthetic restorations. The aim of this study was to assess the deformation of addition and condensation silicone impressions after disinfection in antimicrobial solutions. Methods. A total of 120 impressions were made on the model of the upper arch representing three full metal-ceramic crown preparations. Four impression materials were used: two condensation silicones (Oranwash L - Zhermack and Xantopren L Blue - Heraeus Kulzer) and two addition silicones (Elite H-D + regular body - Zhermack and Flexitime correct flow - Heraeus Kulzer). After removal from the model the impressions were immediately immersed in appropriate disinfectant (gluta-raldehyde, benzalkonium chloride - Sterigum and 5.25% NaOCl) for a period of 10 min. The control group consisted of samples that were not treated with disinfectant solution. Consecutive measurements of identical impressions were realized with a Canon G9 (12 megapixels, 2 fps, 6x/24x), and automated with a computer Asus Lamborghini VX-2R Intel C2D 2.4 GHz, by using Remote Capture software package, so that time-depending series of images of the same impression were obtained. Results. The dimensional changes of all the samples were significant both as a function of time and the applied disinfectant. The results show significant differences of the obtained dimensional changes between the group of condensation silicones and the group of addition silicones for the same time, and the same applied disinfectant (p = 0.026, F = 3.95). Conclusion. The greatest dimensional changes of addition and condensation silicone impressions appear in the first hour after their separation from the model.